2019
DOI: 10.1136/bmjopen-2019-031305
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of and attitudes toward clinical trials in Saudi Arabia: a cross-sectional study

Abstract: ObjectivesClinical trials (CTs) are considered an important method for developing new treatments and providing access to potentially effective drugs that are still under investigation. Measuring the public’s knowledge of and attitudes toward CTs is important for assessing their readiness for and acceptance of human drug testing, which has previously not been assessed in the Kingdom of Saudi Arabia (KSA). The objective of this study is to explore the Saudi public’s knowledge of and attitudes toward CTs as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 27 publications
(51 reference statements)
4
19
5
Order By: Relevance
“…Consistent with other studies, female gender, higher education and previous CT participation were identified as independent factors predicting positive attitude, however, controversial data are also available 18,22‐24 …”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Consistent with other studies, female gender, higher education and previous CT participation were identified as independent factors predicting positive attitude, however, controversial data are also available 18,22‐24 …”
Section: Discussionsupporting
confidence: 81%
“…Male gender, higher education, being younger and healthy were independently associated with better knowledge. The positive influence of the aforementioned demographics on knowledge has been similarly observed, however some previous studies could not find such association 8,18‐22 …”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations